2023
DOI: 10.3892/mmr.2023.13080
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol attenuates human parvovirus B19 NS1‑induced NLRP3 inflammasome activation in macrophages

Chang-Lun Huang,
Der-Yuan Chen,
Chih-Chen Tzang
et al.

Abstract: Human parvovirus B19 (B19V) has been strongly associated with a variety of inflammatory disorders, such as rheumatoid arthritis (RA), inflammatory bowel disease and systemic lupus erythematosus. non-structural protein 1 (nS1) of B19V has been demonstrated to play essential roles in the pathological processes of B19V infection due to its regulatory properties on inflammatory cytokines. Celastrol, a quinone methide isolated from Tripterygium wilfordii, has displayed substantial potential in treating inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Celastrol, a natural product isolated from Tripterygium wilfordii , has displayed therapeutic potential in inflammatory diseases, such as RA. One recent study showed the attenuating effects of celastrol on parvovirus B19-NS1-induced NLRP3 inflammasome activation in macrophages [ 132 ]. Jing et al also revealed that celastrol inhibited inflammation by inhibiting the reactive oxygen species NF-κB-NLRP3 inflammasome axis and relieved RA symptoms [ 133 ].…”
Section: Therapeutic Potential By Targeting the Nlrp3 Inflammasomementioning
confidence: 99%
“…Celastrol, a natural product isolated from Tripterygium wilfordii , has displayed therapeutic potential in inflammatory diseases, such as RA. One recent study showed the attenuating effects of celastrol on parvovirus B19-NS1-induced NLRP3 inflammasome activation in macrophages [ 132 ]. Jing et al also revealed that celastrol inhibited inflammation by inhibiting the reactive oxygen species NF-κB-NLRP3 inflammasome axis and relieved RA symptoms [ 133 ].…”
Section: Therapeutic Potential By Targeting the Nlrp3 Inflammasomementioning
confidence: 99%